2001 : a space odyssey [videorecording (DVD)] - Kubrick, Stanley; Clarke, Arthur C. (Arthur Charles), 1917-2008; Dullea, Keir, 1936-; Lockwood, Gary, 1937-; Sylvester, William, 1922-1995 (Warner Home Video, 2007)
A space voyage to Jupiter erupts in disaster when the ship's computer goes mad.